Comparative transcriptome analysis of the metal hyperaccumulator Noccaea caerulescens - Halimaa, Pauliina; Blande, Daniel; Aarts, Mark G. M.; Tuomainen, Marjo; Tervahauta, Arja; Kärenlampi, Sirpa (Frontiers in Plant Science, 2014)
The metal hyperaccumulator Noccaea caerulescens is an established model to study the adaptation of plants to metalliferous soils. Various comparators have been used in these studies. The choice of suitable comparators is important and depends on the hypothesis to be tested and methods to be used. In high-throughput analyses such as microarray, N. caerulescens has been compared to non-tolerant, non-accumulator plants like Arabidopsis thaliana or Thlaspi arvense rather than to the related hypertolerant or hyperaccumulator plants. An underutilized source is N. caerulescens populations with considerable variation in their capacity to accumulate and tolerate metals. Whole transcriptome sequencing (RNA-Seq) is revealing interesting variation in their gene expression profiles. Combining physiological characteristics of N. caerulescens accessions with their RNA-Seq has a great potential to provide detailed insight into the underlying molecular mechanisms, including entirely new gene products. In this review we will critically consider comparative transcriptome analyses carried out to explore metal hyperaccumulation and hypertolerance of N. caerulescens, and demonstrate the potential of RNA-Seq analysis as a tool in evolutionary genomics.